From Legal Formalism to Algorithmic Justice: Rethinking Consumer Protection in the Digital Economy - Prihartanto, Yudi; Arifin, Firdaus; Maarif, Ihsanul; Kwarteng, Abdul Hamid (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2025)
The rapid expansion of the digital economy has challenged traditional notions of consumer protection, which historically relied on reactive and positivist legal principles. Increasing data commodification, the pervasive role of algorithms, and structural power asymmetries expose the inadequacy of existing legal doctrines to safeguard fairness in digital transactions. This study seeks to address a critical research gap by reconceptualizing consumer protection law through the lens of algorithmic justice and participatory digital rights. Employing a normative legal methodology combined with comparative and critical approaches, the research analyzes doctrinal evolution across jurisdictions such as the European Union, Brazil, and Indonesia. The findings reveal three major shifts. First, consumer law must move beyond post-transaction liability toward proactive models of oversight, including algorithm audits and design-based compliance. Second, legal doctrines should redefine the consumer as a relational subject embedded in data-driven ecosystems, rather than a rational and autonomous actor. Third, consumer rights need to be embedded within constitutional and ethical frameworks to ensure long-term enforceability and democratic legitimacy. The study contributes theoretically by advancing an interdisciplinary paradigm of consumer law that integrates digital fairness, equity, and human dignity. Practically, it offers strategic directions for regulators and policymakers in designing responsive frameworks that anticipate risks, enhance accountability, and strengthen consumer agency in the digital era.